2013
DOI: 10.1007/s00216-013-7042-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of GC stationary phases for the separation of fatty acid methyl esters in biodiesel fuels

Abstract: The fatty acid methyl ester (FAME) content of biodiesel fuels has traditionally been determined using gas chromatography with a polar stationary phase. In this study, a direct comparison of the separation of FAMEs present in various biodiesel samples on three polar stationary phases and one moderately polar stationary phase (with comparable column dimensions) was performed. Retention on each column was based on solubility in and polarity of the phase. Quantitative metrics describing the resolution of important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…After various studies, the DB-WAX column was shown to provide a better resolution than the other two columns, HP-88 and HP-5MS, implying that a high-polar stationary phase is necessary to attain an adequate separation of fatty acids. A similar outcome was reported by Goding et al, 18 who studied the effect of GC column stationary phase on separation efficiency of fatty acids in biodiesel fuels. Figure 1 shows the GC chromatogram of fatty acids in coffee oil (A) and algae oil (B) by using a DB-WAX column and GC conditions shown in the "Materials and methods" section.…”
supporting
confidence: 85%
“…After various studies, the DB-WAX column was shown to provide a better resolution than the other two columns, HP-88 and HP-5MS, implying that a high-polar stationary phase is necessary to attain an adequate separation of fatty acids. A similar outcome was reported by Goding et al, 18 who studied the effect of GC column stationary phase on separation efficiency of fatty acids in biodiesel fuels. Figure 1 shows the GC chromatogram of fatty acids in coffee oil (A) and algae oil (B) by using a DB-WAX column and GC conditions shown in the "Materials and methods" section.…”
supporting
confidence: 85%
“…Other polar columns such as ZB-WAX plus and ZB-FFAP with dimensions of 30 m  0.25 mm  0.25 μm [40] allow a complete separation of 36 of the 37 fatty acids, except for the C18:1cis/transisomers, whereas for the more polar column BPX70, that is a cyanopropyl stationary phase, the separation of the 37 fatty acids is achieved.…”
Section: Retention Behavior Of Famesmentioning
confidence: 99%
“…Separations were performed using an Agilent 6890 gas chromatograph coupled with an Agilent 5937 mass spectrometer (Agilent Technologies, Santa Clara, CA) and have been presented in detail previously [3].…”
Section: Instrumentationmentioning
confidence: 99%
“…A variety of biodiesel feedstock sources, including soybean oil, waste grease, canola oil, and animal tallow were evaluated using chemometric methods. The cyanopropyl column chemistry (BPX70) was utilized for this investigation, as it provided the most optimal separation of individual FAME isomers [3]. The correlation coefficients between several key pairs of biodiesels, using the six most abundant peak areas in each biodiesel, are shown in Table 1.…”
Section: Evaluation Of Biodiesel Feedstock Sourcementioning
confidence: 99%
See 1 more Smart Citation